Neonatal small bowel obstruction due to malrotation: a clinical study - S., Srinivas; K. R., Reddy; T. A., Balraj; A., Gangadhar (International Surgery Journal, 2017)
Background:This study was done at Niloufer hospital and institute of child health, Hyderabad with an aim of evaluating the clinical presentation, diagnostic evaluation, management and outcome of malrotation of intestines in the neonates. Methods: Cases of neonatal small intestinal obstruction due to malrotation presenting to the Department of Pediatric Surgery, Niloufer hospital over a period of two years were evaluated. Results: A total of 38 newborns presented to our department with intestinal obstruction due to malrotation. 3/38 patients presented with extensive gangrene of midgut. 4/38 patients died during the course of treatment. Conclusions: Malrotation is a relatively common cause of neonatal small bowel obstruction. A high index of suspicion is needed in neonates presenting with bilious vomiting. Early laparotomy prevents fatal complication of extensive gangrene due to midgut volvulus.